2012
DOI: 10.1021/cm2036844
|View full text |Cite
|
Sign up to set email alerts
|

Cation Exchange: A Facile Method To Make NaYF4:Yb,Tm-NaGdF4 Core–Shell Nanoparticles with a Thin, Tunable, and Uniform Shell

Abstract: Cation exchange was performed on up-conversion NaYF4:Yb,Tm nanoparticles, resulting in NaYF4:Yb,Tm-NaGdF4 core–shell nanoparticles as indicated by electron energy-loss spectroscopy 2D mapping. Results show that core–shell nanoparticles with a thin, tunable, and uniform shell of subnanometer thickness can be made via this cation exchange process. The resulting NaYF4:Yb,Tm-NaGdF4 core–shell nanoparticles have an enhanced up-conversion intensity relative to the initial core nanoparticles. As potential magnetic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
118
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(119 citation statements)
references
References 40 publications
(80 reference statements)
0
118
1
Order By: Relevance
“…Although the doping of Mn 4 þ has been realized in oxide compounds through solid-state reaction at high temperature, it is unpractical for synthesizing Mn 4 þ -activated fluoride compounds through this route because hazard and corrosive HF gas was used to prevent the oxidation of products 40 . In contrast, cation exchange reaction has been proved to be a convenient method for lanthanide doping in nano-sized fluoride crystals 41,42 . It was well established that efficient cation exchange can only take place in nano-sized materials 43,44 .…”
Section: Resultsmentioning
confidence: 99%
“…Although the doping of Mn 4 þ has been realized in oxide compounds through solid-state reaction at high temperature, it is unpractical for synthesizing Mn 4 þ -activated fluoride compounds through this route because hazard and corrosive HF gas was used to prevent the oxidation of products 40 . In contrast, cation exchange reaction has been proved to be a convenient method for lanthanide doping in nano-sized fluoride crystals 41,42 . It was well established that efficient cation exchange can only take place in nano-sized materials 43,44 .…”
Section: Resultsmentioning
confidence: 99%
“…[29][30][31][32][33][34][35] Recently, cation exchange has been developed to prepare core-shell particles. Dong et al [36] reported a cation exchange route for the upconversion of NaYF 4 :Yb,Tm nanoparticles, resulting in NaYF 4 :Yb,Tm-NaGdF 4 core-shell nanoparticles. Similarly, Zhang et al [37] reported the transformation of singlecrystalline cadmium sulfide nanowires into composition-controlled Zn x Cd (1-x) S nanowires, core-shell heterostructures, metal-semiconductor superlattices (Zn-Zn x Cd (1-x) S), single-crystalline ZnS nanotubes, and even metallic Zn nanowires.…”
Section: Introductionmentioning
confidence: 99%
“…18 Typically, in a 100 mL three-neck O] were added, followed by the addition of 6 mL oleic acid and 15 mL octadecene. After a 30 min stirring under argon flowing at room temperature, this mixture was heated to 160 uC for 30 min to make a clear solution.…”
Section: Synthesis Of Nayf 4 :Yb Tm Core Ucnpsmentioning
confidence: 99%